Feasibility of the preparation of cochleate suspensions from naturally derived phosphatidylserines - Kristensen, Søren; Hassan, Khadeija; Andersen, Nadia Skarnager; Steiniger, Frank; Kuntsche, Judith (Frontiers in Medical Technology, 2023)
Cochleates are cylindrical particles composed of dehydrated phospholipid bilayers. They are typically prepared by addition of calcium ions to vesicles composed of negatively charged phospholipids such as phosphatidylserines (PS). Due to their high physical and chemical stability, they provide an interesting alternative over other lipid-based drug formulations for example to improve oral bioavailability or to obtain a parenteral sustained-release formulation. In the present study, the feasibility to prepare cochleate suspensions from soy lecithin-derived phosphatidylserines (SPS) was investigated and compared to the "gold standard" dioleoyl-phosphatidylserine (DOPS) cochleates. The SPS lipids covered a large range of purities between 53 and >96% and computercontrolled mixing was evaluated for the preparation of the cochleate suspensions. Electron microscopic investigations were combined with small-angle X-ray diffraction (SAXD) and Laurdan generalized polarization (GP) analysis to characterize particle structure and lipid organization. Despite some differences in particle morphology, cochleate suspensions with similar internal lipid structure as DOPS cochleates could be prepared from SPS with high headgroup purity (≥ 96%). Suspensions prepared from SPS with lower purity still revealed a remarkably high degree of lipid dehydration and well-organized lamellar structure. However, the particle shape was less defined, and the typical cochleate cylinders could only be detected in suspensions prepared with higher amount of calcium ions. Finally, the study proves the feasibility to prepare suspensions of cochleates or cochleate-like particles directly from a calcium salt of soy-PS by dialysis.